Physical working capacity and autonomous regulation balance in myocardial infarction patients during long-term out-patient rehabilitation - G. G. Efremushkin; A. G. Akimochkina; A. A. Efremushkina (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To assess the impact of systematic controlled physical training (PT) at the out-patient clinic on physical working capacity (PWC) and autonomous balance in myocardial infarction (MI) patients. Results. PT for 6 and 12 months increased PWC, in correlation with parasympathetic activation and sympathetic inhibition, starting at 6 months and existing for at least 12 months of out-patient rehabilitation in Sub-groups B1 and B2. Long-term adaptation mechanisms provided sustainable benefits in patients trained for 6 months, till 12 months. Conclusion. In out-patient rehabilitation of MI patients, optimal PT duration is 6 months.